Respuesta :

Answer:

The value of [tex]gf\left(-2\right)[/tex] will be:

  • [tex]gf\left(-2\right)=29[/tex]

Step-by-step explanation:

Given the functions

[tex]f(n) = n^2 - 4n + 3[/tex]

[tex]g\left(n\right)\:=\:2n\:-\:1[/tex]

[tex]f\left(-2\right)\:=\:\left(-2\right)^2\:-\:4\left(-2\right)\:+\:3[/tex]

           [tex]=\left(-2\right)^2+4\cdot \:2+3[/tex]

           [tex]=2^2+4\cdot \:2+3[/tex]

            [tex]=2^2+8+3[/tex]

            [tex]=4+11[/tex]

            [tex]=15[/tex]

so

[tex]gf\left(-2\right)=g\left(15\right)[/tex]

             [tex]=2n-1=2\left(15\right)-1=30-1=29[/tex]

Therefore,

  • [tex]gf\left(-2\right)=29[/tex]